Immunosuppressive effects of sialostatin L1 and L2 isolated from the taiga tick Ixodes persulcatus Schulze - Sajiki, Y.; Konnai, S.; Ochi, A.; Okagawa, T.; Githaka, Naftaly W.; Isezaki, M.; Yamada, S.; Ito, T.; Ando, S.; Kawabata, H.; Logullo, C.; Silva Vaz, I. da; et al. (Elsevier, 2020)
Tick saliva contains immunosuppressants which are important to obtain a blood meal and enhance the infectivity of tick-borne pathogens. In Japan, Ixodes persulcatus is a major vector for Lyme borreliosis pathogens, such as Borrelia garinii, as well as for those causing relapsing fever, such as B. miyamotoi. To date, little information is available on bioactive salivary molecules, produced by this tick. Thus, in this study, we identified two proteins, I. persulcatus derived sialostatin L1 (Ip-sL1) and sL2 (Ip-sL2), as orthologs of I. scapularis derived sL1 and sL2. cDNA clones of Ip-sL1 and Ip-sL2 shared a high identity with sequences of sL1 and sL2 isolated from the salivary glands of I. scapularis. Semi-quantitative PCR revealed that Ip-sL1 and Ip-sL2 were expressed in the salivary glands throughout the life of the tick. In addition, Ip-sL1 and Ip-sL2 were expressed even before the ticks started feeding, and their expression continued during blood feeding. Recombinant Ip-sL1 and Ip-sL2 were developed to characterize the proteins via biological and immunological analyses. These analyses revealed that both Ip-sL1 and Ip-sL2 had inhibitory effects on cathepsins L and S. Ip-sL1 and Ip-sL2 inhibited the production of IP-10, TNFα, and IL-6 by LPS-stimulated bone-marrow-derived dendritic cells (BMDCs). Additionally, Ip-sL1 significantly impaired BMDC maturation. Taken together, these results suggest that Ip-sL1 and Ip-sL2 confer immunosuppressive functions and appear to be involved in the transmission of pathogens by suppressing host immune responses, such as cytokine production and dendritic cell maturation. Therefore, further studies are warranted to investigate the immunosuppressive functions of Ip-sL1 and Ip-sL2 in detail to clarify their involvement in pathogen transmission via I. persulcatus.